Cold versus hot endoscopic mucosal resection for large sessile colon polyps: a cost-effectiveness analysis - Mehta, Dhairya; Loutfy, Adam H.; Kushnir, Vladimir M.; Faulx, Ashley L.; Smith, Zachary L. (Endoscopy, 2021)
Background For large sessile colorectal polyps (LSCPs), endoscopic mucosal resection without diathermy (“cold endoscopic mucosal resection [EMR]”) is gaining popularity because of its safety advantages over conventional EMR (“hot EMR”). Polyp recurrence rates have been reported to be higher with cold EMR. Considering these differences, we performed a cost-effectiveness analysis of these two techniques.Methods A decision analysis model was constructed for EMR of an LSCP. The decision tree incorporated the EMR method, clip use, procedural mortality, adverse events and their management, and polyp recurrence. Outcomes included days of lost productivity and marginal cost difference. Adverse event and recurrence rates were extracted from the existing literature, giving emphasis to recent systematic reviews and randomized controlled trials.Results Through 30 months of follow-up, the average cost of removing an LSCP by cold EMR was US$5213, as compared to $6168 by hot EMR, yielding a $955 cost difference (95 % confidence interval $903–$1006). Average days of lost productivity were 6.2 days for cold EMR and 6.3 days for hot EMR. This cost advantage remained over several analyses accounting for variations in recurrence rates and clip closure strategies. Clip cost and LSCP recurrence rate had the greatest and the least impacts on the marginal cost difference, respectively. Conclusion Cold EMR is the dominant strategy over hot EMR, with lower cost and fewer days of lost productivity. In theory, a complete transition to cold EMR for LSCPs in the USA could result in an annual cost saving approaching US$7 million to Medicare beneficiaries.